Periderm invasion contributes to epithelial formation in the teleost pharynx - Teixeira Rosa, Joana; Oralová, Veronika; Larionova, Daria; Eisenhoffer, G T; Eckhard Witten, P; Huysseune, Ann (Scientific reports, 2019)
The gnathostome pharyngeal cavity functions in food transport and respiration. In amniotes the mouth and nares are the only channels allowing direct contact between internal and external epithelia. In teleost fish, gill slits arise through opening of endodermal pouches and connect the pharynx to the exterior. Using transgenic zebrafish lines, cell tracing, live imaging and different markers, we investigated if pharyngeal openings enable epithelial invasion and how this modifies the pharyngeal epithelium. We conclude that in zebrafish the pharyngeal endoderm becomes overlain by cells with a peridermal phenotype. In a wave starting from pouch 2, peridermal cells from the outer skin layer invade the successive pouches until halfway their depth. Here the peridermal cells connect to a population of cells inside the pharyngeal cavity that express periderm markers, yet do not invade from outside. The latter population expands along the midline from anterior to posterior until the esophagus-gut boundary. Together, our results show a novel role for the periderm as an internal epithelium becomes adapted to function as an external surface.
Keywords: geneticky modifikovaná zvířata; dánio pruhované; Animals, Genetically Modified; Animals; Zebrafish; Gills; žábry; Endoderm; zvířata; endoderm; farynx; Pharynx